APLIKASI MEDIA GAMBAR BERSERI PADA PEMBELAJARAN TEMATIK TERPADU KELAS IV SEMESTER II TEMA PAHLAWANKU SD NEGERI BOLO DEMAK - Kiswoyo Kiswoyo; Nurul Ariyanti (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2015)
This research is motivated by the lack of media use are causing varying levels of students' understanding of the material becomes less , and students feel tired and less interested in learning a given.The problem in this study is How the media application on the radiant image of integrated thematic teaching fourth grade second semester Elementary School Heroes theme Bolo Demak in the Academic Year 2013/2014? The purpose of this study was to describe the radiant image media applications on integrated thematic learning fourth grade second semester Elementary School Heroes theme Bolo Demak in the Academic Year 2013/2014.This research uses descriptive qualitative research approach. Location of the study in Demak Bolo Elementary School fourth grade second semester. Data sourced words research results.The results showed no improvement in student evaluation of learning outcomes 4, 5, and 6 using media images beamed on learning Heroes theme. The average value of classical ie increased 85,7 % which exceeds the results of complete classical limit above 75% of all students. Observations of teachers learning to use the media images have an average radiant with the criteria of "good" by 70%. Observation results showed no increase in students attitudes change in the behavior of students in learning 6, ie, there are 30 students from 35 students or completeness of 85,7% in the classical with the very good category.The response of the students and teachers to use instructional media images beamed ie, most of the students are very excited and interested in learning more active, very enthusiastic and serious in doing. The advice given researchers, classroom teachers should use the media image series in learning, students should follow the lessons well, so that learning can take place in a conducive